Explaining the May 9th Regime Change in Malaysia: Ethnic Boundary, Social Differentiation, National Ethos and Political - Noor , Mansor Mohd (South Asian Journal of Social Sciences and Humanities, 2020)
Malaysia is a product of a post-colonial plural society. However, under the influences of  development, migration and technological changes, the plural society characters of the nation  have undergone social transformation from one of a compartmentalized society by language,  culture, religion and economic vocation into a diverse society. However, the conceptual and  theoretical frameworks of the tradition of Furnivall’s plural society may not be able to explain  the fluidity and dynamism of contemporary Malaysia. Ethnic and religious dimensions may  define the ethnicised society but to argue that such a society is a plural society may not do  justice to explain the shift from ethno-religious concerned are being embedded with civic  spaces of justice, inclusivity and participative democracy of the Malaysian diverse society.  This article grapples with the constraints of the Furnivall tradition by introducing the  conceptual framework of ethnic boundary in the tradition of Barth and the theoretical  framework of the sociology of modernization and development in understanding and  explaining the social changes taking place in Malaysia. Ethnic identity still prevails but it has  thinned as an influence on social action. Studies show that social cohesion dominates the  relationship of the diverse ethnic groups that shared a common norm, showing greater  similarities rather than differences and under such social differentiation in the society, they  relate to one another horizontally and least vertically.
Keywords: Plural Society; Ethnic Boundary; Social Differentiation; Nation